THE EFFECT OF PLAYING A COMPUTER-BASED DETECTIVE GAME IN IMPROVING VOCABULARY MASTERY OF SENIOR HIGH SCHOOL STUDENTS - Aam Ali Rahman, - (2008)
This is an experimental study of the effect of playing a computer-based detective game on students' vocabulary mastery in SMK Negeri 4 Padalarang, Bandung. The title of the game played is Nancy Drew; The Creature of Kapu Cave. This game is developed by HeR Interactive, Simon and Scluster Inc. 2006. This research aimed to investigate the effect of playing computer game on the development of students' vocabulary mastery, and also its significant level statistically. Theoretically, this research was held to serve another method of teaching vocabulary to students and it is hoped that this research can add new concept of vocabulary teaching. SMK Negeri 4 Padalarang has been chosen as sample for this research, since they provide computer-skilled program. So, it was presumed that samples do not face difficulty in operating computer. There were two classes conducted as samples; experimental class and control class. This research used comparative analysis by using t-test calculation to compare the result of post-test of experimental class and control class. In addition, it aimed to seek the significance different of both classes in mastering vocabulary after receiving different treatment. From the result of the research, it was known that tobt equals with 2.572665. This t-test result is significant on the level 0.05 for degree of freedom equals with 60, since the value of t-test score needed is about 2.000. So, based on the result, the null-hypothesis is rejected. It means that after receiving treatment, both classes are statistically different; experimental class tends to has better score than control class. In sum, based on the result of the research, it is proven that to some extent this method is effective to develop students' vocabulary mastery.